The Age Structure, Stringency Policy, Income, and Spread of Coronavirus Disease 2019: Evidence From 209 Countries - Bilgili, Faik; Dundar, Munis; Kuşkaya, Sevda; Lorente, Daniel Balsalobre; Ünlü, Fatma; Gençoğlu, Pelin; Muğaloğlu, Erhan (Frontiers in Psychology, 2021)
This article aims at answering the following questions: (1) What is the influence of age structure on the spread of the COVID-19? (2) What can be the impact of stringency policy (policy responses to the Coronavirus pandemic) on the spread of COVID-19? (3) What might be quantitative effect of development level-income and number of hospital beds on the number of deaths due to the COVID-19 epidemic? By employing the methodologies of GLM, GMM, and quantile regression models, this paper reveals that the shares of median aged, aged-65 and aged-70, and older-aged population have significant positive impacts on the spread of COVID and that share of aged-70 and older-aged people in the population has the relatively greater influence on the spread of the pandemic. The second output of this research is the significant impact of stringency policy on diminishing the COVID-19 total cases. The third finding of this paper reveals that the number of hospital beds appears to be vital in reducing the total number of COVID-19 deaths while GDP per capita does not affect much the level of deaths of the COVID-19 pandemic. Finally, this paper suggests some governmental health policies to control and decrease the spread of COVID-19.